Development and evaluation of clove oil nanoemulsion-based topical cream for anti-inflammatory activity in mice - Shafiq, Ahsan; Baboo, Irfan; Farooq, Zahid; Majeed, Hamid; Palangi, Valiollah (Frontiers in Veterinary Science, 2025)
IntroductionInflammatory skin disorders require effective topical therapies with minimal side effects. Clove (Syzygium aromaticum) is recognized for its potent anti-inflammatory, antimicrobial, and antioxidant properties, but it has a limited clinical use due to its highly volatile nature, poor solubility, and potential skin irritation at higher concentrations. This research aimed to develop and optimize clove oil nanoemulsion (CONE)-based topical cream, characterize its physicochemical properties, and evaluate anti-inflammatory efficacy using a mouse model.Methodology & ResultsCONE was prepared via ultrasonication and optimized using response surface methodology. The optimized CONE exhibited a mean droplet size of approximately 190 nm and Polydispersity Index of 0.08, with high entrapment efficiency (94.54%). GC-MS analysis confirmed eugenol as the major constituent. The nanoemulsion demonstrated strong antifungal activity. The minimum inhibitory concentration was 120 μl/mL. CONE significantly enhanced antioxidant capacity compared to clove oil. The cream was formulated by incorporating CONE into carboxymethyl cellulose (CMC) matrix and evaluated for stability, pH, morphology, and drug release. The cream maintains stability, favorable organoleptic properties, and sustained drug release, particularly at a 1 mL CONE concentration. Thirty adult male albino mice (30–40g) were used and randomly divided into six groups. Hematological parameters and C-reactive protein level further supported the anti-inflammatory efficacy topical cream, with marked improvements observed in treated groups. Histopathological analysis revealed re-epithelialization and diminished inflammatory infiltration.ConclusionCONE-based cream offers a promising, safe, and effective topical therapy for inflammatory skin conditions. The nanoemulsion formulation enhances clove oil’s bioavailability, stability, and therapeutic potential, supporting further development for clinical and cosmetic applications.